Management accountancy - Chakraborty, Hrishikesh; Chakraborty, Srijit (Delhi : Oxford University Press, 1997)
Business
Keywords: Accountancy; Management; Cost analysis; Magerial mathematics; Managerial statistics; Managerial graphics; Mangerial economics; Budget; Operational management; Profitability analysis; Financial management